2004
DOI: 10.1093/rheumatology/keh331
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with abnormal Pap results in systemic lupus erythematosus

Abstract: A history of STDs and use of OCs were associated with abnormal Pap reports in this SLE sample. Immunosuppressive exposure may confer further risk to women with SLE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
44
0
9

Year Published

2007
2007
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(55 citation statements)
references
References 21 publications
2
44
0
9
Order By: Relevance
“…Moreover, Bertansky et al found an increase in abnormal cervical cytology in the lupus group vs. controls (P>0.0008). Furthermore, the abnormal cytopathology was accounted for by an excess of HGSIL and cancer (OR = 3.46; P >0.0003) (16,17) .…”
Section: Discussion:-mentioning
confidence: 97%
See 1 more Smart Citation
“…Moreover, Bertansky et al found an increase in abnormal cervical cytology in the lupus group vs. controls (P>0.0008). Furthermore, the abnormal cytopathology was accounted for by an excess of HGSIL and cancer (OR = 3.46; P >0.0003) (16,17) .…”
Section: Discussion:-mentioning
confidence: 97%
“…One study showed an increased incidence of cervical cancer in SLE and other studies have noted a high risk of abnormal Pap tests in women with SLE (4) .…”
Section: Introduction:-mentioning
confidence: 98%
“…Estudios observacionales no han encontrado asociación entre el uso de ACO en LES y el desarrollo de enfermedad vascular periférica (33), nefritis lúpica o cáncer de mama (16), pero sí una mayor frecuencia de Papanicolaou anormal (34).…”
Section: ) (26)unclassified
“…Entre elas, encontram-se: (a) anormalidades intrínsecas do sistema imunológico, decorrentes da própria doença, prejudicando a vigilância antitumoral; (b) presença de doenças associadas ao LES como a síndrome de Sjögren; (c) fatores geográficos, étnicos e raciais comuns a neoplasias e ao LES; (d) medicações utilizadas no tratamento do LES como azatioprina, metotrexato e ciclofosfamida; (e) interações entre as medicações e exposições virais (1,(6)(7)(8)(9) . Neoplasias de colo uterino incidem em 20/100.000 mulheres nas Regiões Sul e Sudeste do Brasil (10) .…”
Section: Introductionunclassified
“…Neoplasias de colo uterino incidem em 20/100.000 mulheres nas Regiões Sul e Sudeste do Brasil (10) . Lesões malignas (e pré-malignas) de cérvix uterina fazem parte dos tumores descritos como sendo mais prevalentes no LES (6,8,9) . Esse aspecto pretende ser explorado no presente estudo que tem por objetivo estabelecer a freqüência de alterações no esfregaço citopatológico (Papanicolaou) em uma população local de pacientes com LES e verificar se tal aumento está associado ao uso de medicações, tempo de doença e perfil de auto-anticorpos apresentado.…”
Section: Introductionunclassified